2021
DOI: 10.18844/cjes.v11i4.1217
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the efficiency of motor learning with the help of video analysis

Abstract: This article deals with the problem of increasing the efficiency in motor learning with the help of video analysis. The text approaches the system providing a feedback in the process of downhill skiing skills acquisition. The platform influencing the movement notion introduces innovative means of the acquisition of essential downhill skiing skills in ski courses organised by the University of Hradec Kralove, the Department of Physical Education (PE) and Sport. This article is focused on the selected results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Ezza, Alhuqail and Elhussain (2019) found that instructional technology significantly enhances learners' composing skills. Ruzicka and Milova (2019) found that the use of video analysis in providing feedback has a positive effect on the process of downhill skiing skills acquisition. Ugwuanyi et al (2019a) found that flipped classroom instructional technology was effective in enhancing the achievement of physics students at both post-test and follow-up measurements.…”
Section: Review Of Related Empirical Studiesmentioning
confidence: 95%
“…Ezza, Alhuqail and Elhussain (2019) found that instructional technology significantly enhances learners' composing skills. Ruzicka and Milova (2019) found that the use of video analysis in providing feedback has a positive effect on the process of downhill skiing skills acquisition. Ugwuanyi et al (2019a) found that flipped classroom instructional technology was effective in enhancing the achievement of physics students at both post-test and follow-up measurements.…”
Section: Review Of Related Empirical Studiesmentioning
confidence: 95%
“…The findings of this study are in line with the findings of Ezzaet al Ezza et al (2019) found that instructional technology could significantly enhance learners' composing skills. Ruzicka and Milova (2019) found that the use of video analysis in providing feedback has a positive effect on the process of downhill skiing skills acquisition. Ugwuanyi et al (2020) found that animated powerpoint presentation (PPT) significantly enhanced the achievement of students in physics than the non-animated PPT presentation.…”
Section: Discussion Of the Findingsmentioning
confidence: 95%
“…Ezza et al (2019) found that instructional technology could significantly enhance learners' composing skills. Ruzicka and Milova (2019) found that the use of video analysis in providing feedback has a positive effect on the process of downhill skiing skills acquisition. Anigbo and Orie (2018) revealed that the experimental group taught with Microsoft PowerPoint Instruction Strategy (MSPPIS) obtained a higher mean achievement score than the control group in the post COSAT but the difference was not significant.…”
Section: Literature Reviewmentioning
confidence: 95%
“…According to Clark and Mayer (2003), animation refers to a computerised simulation of processes using images to structure a synthetic motion picture and adding printed text, charts, maps, static graphics and self-motivated graphics. When used essentially as a form of entertainment, an animation can be a cartoon, but in this study, we focused on the potential of animation as an educational tool (Hamzat, Bello & Abimbola, 2017). According to Hamzat et al (2017), different categories of images with text have diverse functions in creating mental models as a replacement for simply receiving the knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…When used essentially as a form of entertainment, an animation can be a cartoon, but in this study, we focused on the potential of animation as an educational tool (Hamzat, Bello & Abimbola, 2017). According to Hamzat et al (2017), different categories of images with text have diverse functions in creating mental models as a replacement for simply receiving the knowledge. The animation that combines audio and visual features may help in the course of encoding information, storing it into lasting memory and the recovery process (Paivio as cited in Hamzat et al, 2017).…”
Section: Introductionmentioning
confidence: 99%